Counselling skills in obstetrics and gynecological patients considering medical, emotional, cultural and legal perspectives: a commentary - Agarwal, Manika; Singh, Kaushiki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Communication is an important skill which doctors must possess in order to deal with patients and build a good rapport with them. It not only increases communication and understanding but also helps to break bad news to the patient with more empathy. In this study we have taken four cases from our hospital where good counselling plays an important role in patient management. We deal with such patients in our routine life and lessons learnt play an important role in dealing with similar patients with ease in future.